Especies forrajeras de corte del género Pennisetum sp. en las características agronómicas y rendimiento en Zungarococha – Perú - Del Aguila Pua, Edwar Brahayan (2025)
The feeding of polygastrics in the tropical zone is a need to produce forage that can cover the needs of meat and milk production and the National University of the Peruvian Amazon considers it a priority and the Faculty of Agronomy is conducting research that can provide an answer to this need of the Amazonian cattle rancher and for this reason presents this research entitled: CUTTING FODDER SPECIES OF THE GENUS Pennisetum sp. IN THE AGRONOMIC CHARACTERISTICS AND YIELD IN ZUNGAROCOCHA - PERU. Performing a randomized block design with plots of 3.6 m2, the treatments under study were T1 (Cuba 22 grass), T2 (Maralfalfa grass), T3 (Green King grass) and T4 (Rodas grass), with the following results It can be concluded that the pastures of the genus Pennisetum sp. They are cut grasses and have the highest aboveground biomass production of the Poaceae family. In the dependent variables such as plant height, treatment T4 (Rodas grass) showed the greatest height at 2.41 meters. Green matter was 4.82 kg/m2, dry matter 1.06 kg/m2, coverage percentage 96.15%, leaf weight 1.58 kg/m2, and stem weight 3.28 kg/m2. The yield per hectare per cut was 48,500 kg/ha.